Pengaruh Penyuluhan Personal Hygiene Pada Warga RT 11 RW 03 Kelurahan Lempuing Kecamatan Ratu Agung Kota Bengkulu - Nopia Wati; Agus Ramon; Hasan Husin; Fiana Pondesta; Rezatul Putri (Gayaku Publisher, 2023)
Maintenance of personal hygiene is necessary both for individual comfort, safety, and health. Area coastal is one of the marine waters environment easily affected by the discharge of waste from land. Methods and community service activities used pre-experiment with a re-treatment design (one group pre and post test design). Counseling was held on December 19, 2022. Based on the dedication that has been carried out in Rt.11 Rw.03 Lempuing Village, Ratu District Agung Bengkulu City about personal hygiene at coastal communities, it can be concluded that there is influence counseling on increasing the knowledge of residents of Rt.11 Rw.03 Lempuing Village, Ratu Agung City District Bengkulu.